Optimized QuEChERS-HPLC-MS/MS method for pesticide residue detection in strawberries and associated health risks - Hasti Gordan; Vahideh Mahdavi; Moslem Basij; Amin Mousavi Khaneghah (Journal of Agriculture and Food Research)
A quick, easy, cheap, effective, rugged, and safe (QuEChERS)-based sample preparation method coupled with ultra-high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) in dynamic multiple reaction monitoring (dMRM) mode was developed to determine the residues of the 35 most applied pesticides in strawberry greenhouses in Iran. The process was validated, and the linear dynamic range (LDR) of matrix-matched calibration curves was 0.005–0.5 mg/kg, with determination coefficients (R2) greater than 0.99. The limits of detection (LOD) and quantification (LOQ) of the method were in the range of 0.0001–0.0059 mg/kg and 0.0003–0.0197 mg/kg, respectively. Furthermore, the accuracy and precision were studied at two concentration levels. The recoveries ranged from 70 % to 125 %, and the relative standard deviations (RSD%) for the three replicates were lower than 10 % for all analytes. The developed method was applied to 46 strawberry samples collected from Jiroft greenhouses in Kerman Province, and six pesticide residues were found at concentration levels exceeding maximum residue limits (MRLs), including five fungicides: thiophanate methyl, carbendazim, penconazole, azoxystrobin, and iprodione, and one insecticide: profenofos. The Monte Carlo simulation (MCS)-based health risk assessment indicates that pesticide residues in strawberries, even at concentrations higher than the permissible limit, will not cause long-term health problems for adult and child consumers due to the low per capita consumption. Extending the pre-harvest intervals (PHI) or decreasing the application rates is recommended to minimize the amount of residue and potential hazards.